World Economic Outlook July Update 2022. (World Economic Outlook; World Economic Outlook ;, 2022)
A tentative recovery in 2021 has been followed by increasingly gloomy developments in 2022 as risks began to materialize. Global output contracted in the second quarter of this year, owing to downturns in China and Russia, while US consumer spending undershot expectations. Several shocks have hit a world economy already weakened by the pandemic: higher-than-expected inflation worldwide--especially in the United States and major European economies--triggering tighter financial conditions; a worse-than-anticipated slowdown in China, reflecting COVID- 19 outbreaks and lockdowns; and further negative spillovers from the war in Ukraine.